Sikap Kesombongan dan Kejahatan Iblis dalam Al-Qur’an dan Relevansinya di Zaman Sekarang: Sebuah Kajian Tematik - Hubby Dzikrillah Alfani, Ilzam; Mukhsin, Mukhsin; Addzaky, Khoirul Umam (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2024)
This study aims to review the pride and evil of the devil in the Qur'an and relate it to today's times. This research uses a qualitative method by relying on various literature. The data is analyzed descriptively. This study concludes that the devil is a creature of the jinn who has ghuluw characteristics including arrogance, evil, and disobedience to Allah's commands. The consequence of the devil's ghuluw nature is humiliation and kufr. Then, the relevance of the devil's arrogant and evil attitude to today, the emergence of phenomena that are not in accordance with religious and state norms such as the Pursuit of Power and Fame, Vanity in the Digital Age, Materialism and Greed, Polarization and Online Hatred, and Neglect of Moral Responsibility.